An introduction to mountain glaciers as climate indicators with spatial and temporal diversity - Winkler, Stefan; Chinn, Trevor; Gärtner-Roer, Isabelle; Nussbaumer, Samuel U.; Zemp, Michael; Zumbühl, Heinz J. (ERDKUNDE, 2010)
This article gives an introduction to the spatial and temporal diversity of mountain glaciers as climate indicators. Alongside some information about the present extent of mountain glaciation and available databases, some specific problems with the interpretation of mountain glacier changes are highlighted.